Common Fixed Point Theorems for OWC Maps Satisfying Property (E.A) in S-Metric Spaces Using an Inequality Involving Quadratic Terms - Rao, V. Sambasiva; Dixit, Uma (Communications in Mathematics and Applications, 2022)
In this study, using a quadratic inequality, we prove certain fixed point theorems for four pair wise occasionally weakly compatible maps. In fact, we slightly modify the inequality used by G. V. R. Babu et al. [3, 4] and apply it to S-metric spaces. We also give an example to justify the relevance and reliability of our results.
Keywords: Coincidence points; Common fixed points; Property (E.A); Occasional weak compatibility; Common property (E.A)